Managing social media practices in the digital economy - Alavi, Shirin, 1980-; Ahuja, Vandana (Advances in marketing, customer relationship managemnt, and e-services (AMCRMES) book series, 2020)
""This book facilitates an understanding of diverse social media tools and platforms and their impact on society, business, and the economy and illustrates how online communities can benefit the domains of marketing, finance, and information technology"--Provided by publisher"--